THE IMPORTANCE OF REHABILITATION NURSING IN THE PORTUGUESE INTENSIVE CARE UNITS - Roberto Miguel Gonçalves Mendes; Manuel Lourenço Nunes (Associação Portuguesa dos Enfermeiros de Reabilitação, 2018)
Objective: To know the importance of Rehabilitation Nursing in Portuguese intensive care units (ICUs). Methods: Secondary analysis of the national evaluation survey of the organization of rehabilitation care in Portuguese intensive care units. Results: In Portugal there are 2.9 nurses with specialized training in rehabilitation per unit. This value increases in units where rehabilitation is based on a mixed model and decreases in units that resort to specialized external teams. 40% of these professionals do not perform functions in their area of specialization and only 26.4% perform full-time functions. Units with full-time rehabilitation nursing more frequently assess the physical condition at discharge (38.7 versus 8.9%), however, these professionals do not participate in the post-discharge evaluation in any ICU. There are no observable differences in care outcomes among ICUs that are part of rehabilitation nurses and those who do not. Conclusion: Nurses with a specialty in rehabilitation nursing are present in most of the national ICUs and are an important part of the care provided.